Respiratory virus transmission using a novel viral challenge model: An observational cohort study. Issue 4 (October 2022) - Medina, Marie-jo; Nazareth, Joshua; Dillon, Helen M.; Wighton, Christopher J.; Bandi, Srini; Pan, Daniel; Nicholson, Karl G.; Clark, Tristan W.; Andrew, Peter W.; Pareek, Manish
Highlights: A novel methodology for evaluating transmission of respiratory viruses. It is feasible to recruit children as index cases and adults as contacts and evaluate virus transmission in a healthcare setting. Transmission occurred in 15% of an infected child's contacts following a 30 min controlled interaction. Transmission occurred more commonly when the adult contact was female. Abstract: Objectives: Knowledge of Acute Respiratory virus Infection (ARI) is limited in relation to their substantial global burden. We completed a feasibility study of a novel method to study the natural transmission of respiratory viruses from young children to adults in hospital. Methods: Between September 2012 and May 2015, we recruited healthy adults (contacts) and paediatric inpatients with ARIs (index) presenting to the University Hospitals Leicester NHS Trust, Leicester, UK. We took nose and throat swabs from all participants prior to controlled, 30 minute interactions between the children with ARIs and adult contacts. Contacts recorded symptoms and provided four nose and throat swabs over ten days post-interaction, which were tested for a panel of respiratory viruses to assess transmission. Results: 111 interactions occurred between children with ARIs and adult contacts. Respiratory viruses were detected in 103 of 111 children (93%), most commonly rhinoviruses (RVs) (67 of 103, 65%). Transmission to an adult contact occurred in 15 (14·6%) of 103 interactions and was inversely associated with the contact being male (adjusted OR 0·12; 95% CI 0·02–0·72). Conclusion: Using a novel methodology, we found that natural transmission of ARIs occurred in 15% of an infected child's contacts following a 30 minute interaction, primarily by RVs and when the contact was female. Our model has key advantages in comparison with human challenge studies making it well-suited for further studies of respiratory virus transmission, disease pathogenesis, and clinical and public health interventions to interrupt transmission.